2010
DOI: 10.1044/1058-0360(2010/09-0067)
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Systematic Review: Effects of Oral Motor Interventions on Feeding and Swallowing in Preterm Infants

Abstract: Although some OMIs show promise for enhancing feeding/swallowing in preterm infants, methodological limitations and variations in results across studies warrant careful consideration of their clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(94 citation statements)
references
References 82 publications
3
84
0
7
Order By: Relevance
“…This time might be associated to intercurrences which these preterm born infants suffer with the long period of hospital stay, which might be an inherent factor to the difficulty presented in feeding, so as the presence of neurologic immaturity, the inadequate muscular tonus, the weakness in the oral reflexes and the difficulty of keeping the alert state are factors that might be directly linked in the loss of oral skills in preterm newborns 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This time might be associated to intercurrences which these preterm born infants suffer with the long period of hospital stay, which might be an inherent factor to the difficulty presented in feeding, so as the presence of neurologic immaturity, the inadequate muscular tonus, the weakness in the oral reflexes and the difficulty of keeping the alert state are factors that might be directly linked in the loss of oral skills in preterm newborns 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Such intercurrences favour a prolonged permanence in the Neonatal Intensive Care Unit (NICU), thus inhibiting the success of feeding via the oral route in the appropriate moment 1,2 . In order to benefit the nutritional necessities of the preterm newborn infant, feeding is provided, initially, trough feeding tubes, yet after being released to begin feeding through the oral route, the prolonged use of tubes can interfere with the baby's oral skills 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Non-nutritive oral opportunities are thought to facilitate oral feeding skills, for example, sucking opportunities for preterm infants, most often via pacifier. [17][18][19] Older children who are not safe to take nutrition orally can be given opportunities to mouth toys or to put their fingers into food and suck on their fingers with a miniscule amount of food on them, and to accept two to three drops of water via a spoon. It is rare that a child cannot take anything orally (nil by mouth).…”
Section: Feeding/swallowing Interventions: Evidence Of Effectiveness mentioning
confidence: 99%
“…Pinelli and Symington (2005) report that non nutritive sucking (NNS) was found to decrease significantly the length of hospital stay for preterm infants and had a positive influence on transition from tube to bottle feeds with better bottle feeding performance. Another systematic review has explored direct oral stimulation techniques (Arvedson et al, 2010). This concluded that although oral motor interventions show promise for enhancing feeding and swallowing in preterm infants, there remains no clear direction for clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Oral feeding is a complex skill requiring the integration of breathing, sucking and swallowing in the context of overall motor stability and incoming sensory stimuli (Arvedson et al, 2010;da Costa et al, 2010a). It depends upon brainstem central pattern generators whose activity is increasingly influenced by chemosensory and oral tactile input (Amaizu et al, 2008;Bingham, 2009).…”
Section: Introductionmentioning
confidence: 99%